2012
DOI: 10.1152/japplphysiol.01491.2011
|View full text |Cite|
|
Sign up to set email alerts
|

Two-year citations of JAPPL original articles: evidence of a relative age effect

Abstract: Several indicators have been used to analyze scientific journals, with the impact factor and the number of citations in a 2-yr calendar time frame (2-YRC) being the most common factors. However, considering that the Journal of Applied Physiology (JAPPL) appears monthly and that calculations of these indicators are based on citations of papers published in previous years, we hypothesized that articles published at the beginning of the year would be cited more in the 2-YRC compared with those appearing in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“… 3. Ayres and Vars (2000); Bornmann and Williams (2013); De Araujo et al (2012); Filion and Pless (2008); Frosch et al (2010); Gargouri et al (2010); Georgas and Cullars (2005); Guerrero-Bote and Moya-Anegón (2014). …”
mentioning
confidence: 99%
“… 3. Ayres and Vars (2000); Bornmann and Williams (2013); De Araujo et al (2012); Filion and Pless (2008); Frosch et al (2010); Gargouri et al (2010); Georgas and Cullars (2005); Guerrero-Bote and Moya-Anegón (2014). …”
mentioning
confidence: 99%
“…The US has been the major single contributor to this Scopus category. Articles published 2015-18 were excluded from the citation analysis component because several years are needed for citation counts to stabilise and shrink within-year citation differentials (de Araújo, de Oliveira, de Oliveira Brito, et al, 2012). First and last author genders were detected using a list of gendered first names that has an error rate of 1.5% on US academics but leaves some genders unknown and overestimates the proportion of females by 1% (based on comparisons with human-checked data in: Thelwall et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Within-journal variance in citation numbers across the spectrum of published articles is a further limitation to use of the impact factor, and that is the subject of this editorial. In this issue of the Journal of Applied Physiology, an analysis of one cause of within-journal citation variance is presented by Araujo et al (1). This is the "aging effect."…”
mentioning
confidence: 99%
“…With the impact factor being a number based on average citations to papers published over 12 calendar months, the authors showed that those papers published early in the calendar year receive more citations than those published later in the year. Linear regression of their data (1) shows the decrease in citations is linear month by month from a high of 6.7 in January to a low of 4.8 in December. The reason given is that the longer a paper has been in print, the more likely it is to have garnered citations, all other factors equal.…”
mentioning
confidence: 99%
See 1 more Smart Citation